FACTORS ASSOCIATED WITH MEDICATION ADHERENCE AMONG ISCHEMIC STROKE PATIENTS AT BAKTI TIMAH HOSPITAL, PANGKAL PINANG, IN 2025. - Putri (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Ischemic stroke is the main cause of death in Indonesia, including in the Bangka Belitung area. The level of medication adherence in ischemic stroke patients is still at a low level, which has an impact on the increased risk of recurrence and death. This study aims to determine factors related to medication adherence in ischemic stroke patients, especially at Bakti Timah Pangkalpinang Hospital. The factors studied included knowledge, attitudes, and family support for patients. This study uses a quantitative method with a cross-sectional design. with a sample of 88 respondents were taken from ischemic stroke patients who underwent outpatient treatment at Bakti Timah Pangkalpinang Hospital. The sampling technique used is purposive sampling. Data collection was carried out using a validated questionnaire, namely MMAS-8 to measure medication adherence, as well as a special instrument to measure variables of knowledge, attitudes, and family support. As well as data analysis using the Chi Square test. The results showed that there was a significant relationship between knowledge (p=0.000), attitude (p=0.000), and family support (p=0.000) and medication adherence in ischemic stroke patients. Knowledge, attitude and family support are the factors that most influence the patient's compliance in undergoing treatment. The results of this study can help in developing more effective intervention strategies to improve the quality of life of ischemic stroke patients. The conclusion that can be drawn from this study is that knowledge, attitudes, and family support have a meaningful relationship with the level of compliance of ischemic stroke patients in taking medication. The suggestion from this study is the need for continuous educational interventions to patients and discharges as well as the increasing role of health workers in providing support and monitoring to ischemic stroke patients.